Is Laparoscopic Distal Gastrectomy A Justified Approach for Adult Hypertrophic Pyloric Stenosis, a Rare Cause of Gastric Outlet Obstruction? (with video) - Mehmet Akif Türkoğlu; Mert Ekinci; Ayşenur Sert; Böke Ecenur Alyaz; Feriha Pınar Uyar Gocun (Gazi Medical Journal)
Idiopathic hypertrophic pyloric stenosis (IHPS), which affects 0.2% to 0.4% of children, is caused by the hypertrophy of the pylorus muscle layer. This condition leads to stenosis and non-bilious vomiting. Adult IHPS (AIHPS) is rare and typically occurs in males aged 30-60 years. This report discusses the case of a 39-year-old male diagnosed with IHPS following surgery. The patient, who complained of abdominal swelling, nausea, and vomiting, was diagnosed with gastric outlet obstruction on computed tomography (CT) and upper gastrointestinal endoscopy (UGE). Laparoscopic distal gastrectomy with Roux-en-Y reconstruction was performed due to unsuccessful endoscopic intervention and ongoing symptoms. The pathological diagnosis was consistent with that of IHPS. Laparoscopic distal gastrectomy with Roux-en-Y reconstruction is an effective treatment for AIHPS. It minimizes discomfort, reduces hospital stay and recovery time, and provides definitive diagnoses with minimal invasiveness. Laparoscopic skills are crucial. Further research and extended follow-up are required to confirm standard care for AIHPS.